2005
DOI: 10.1002/lsm.20144
|View full text |Cite
|
Sign up to set email alerts
|

Effectivity of laser-induced thermotherapy: In vivo comparison of arterial microembolization and complete hepatic inflow occlusion

Abstract: Interrupting hepatic perfusion significantly increases lesion volumes in LITT. This beneficial effect can also be achieved in the percutaneous application mode by LITT combined with arterial microembolization via a hepatic artery catheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…33 Owing to those insights, neoadjuvant TACE is a budding possibility for effective downsizing and reduction of the number of metastases, thus making the patients eligible for LITT. 34 In addition, new emerging techniques such as MR-guided high-intensity focused ultrasound, although still facing limitations in the liver due to rib heating, for example, might provide promising alternatives for treatment of hepatic malignancies. A study by Salomir et al 35 suggested a method for rib shielding during deposition of the ultrasound energy through the insertion of a physical mask in the prefocal beam pathway.…”
Section: Discussionmentioning
confidence: 99%
“…33 Owing to those insights, neoadjuvant TACE is a budding possibility for effective downsizing and reduction of the number of metastases, thus making the patients eligible for LITT. 34 In addition, new emerging techniques such as MR-guided high-intensity focused ultrasound, although still facing limitations in the liver due to rib heating, for example, might provide promising alternatives for treatment of hepatic malignancies. A study by Salomir et al 35 suggested a method for rib shielding during deposition of the ultrasound energy through the insertion of a physical mask in the prefocal beam pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Isbert et al also demonstrated in animal experiments that intralesional tumor recurrences develop especially in high vascularized areas within the coagulation zone [44]. In a recent study evaluating the effects of blood flow occlusion in laserinduced thermotherapy, the same histopathological changes were found in lesions created with maintained hepatic perfusion [12]. There was markedly less damage with maintained blood flow than with interrupted perfusion.…”
Section: Discussionmentioning
confidence: 85%
“…Hepatic perfusion leads to a so-called heat sink effect by continuously transporting heat, thus preventing its spread. In previous studies, continuous temperature measurements during ablation showed that heat transport was significantly reduced by completely interrupting hepatic perfusion [12][13][14][15][16]43]. A temperature difference of more than 20°C compared to perfused tissue enlarged the area of thermally exposed cells and subjected them longer to higher cytotoxic temperatures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To reduce the number of complications, attention must be paid to vulnerable structures close to the tumor or the ablation zone. This applies to the porta hepatis, gallbladder, stomach, small intestine and colon, all of which are particularly sensitive to thermal damage [70,71]. In case of subdiaphragmatic lesions, pulmonary, pleural or cardiac heat damage might occur, usually with only minor clinical significance [72,73].…”
Section: Location Of Tumorsmentioning
confidence: 99%